2021
DOI: 10.1186/s13045-021-01055-9
|View full text |Cite
|
Sign up to set email alerts
|

Third-line therapy for chronic myeloid leukemia: current status and future directions

Abstract: Chronic myeloid leukemia (CML) is driven by the BCR-ABL1 fusion protein, formed by a translocation between chromosomes 9 and 22 that creates the Philadelphia chromosome. The BCR-ABL1 fusion protein is an optimal target for tyrosine kinase inhibitors (TKIs) that aim for the adenosine triphosphate (ATP) binding site of ABL1. While these drugs have greatly improved the prognosis for CML, many patients ultimately fail treatment, some requiring multiple lines of TKI therapy. Mutations can occur in the ATP binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 105 publications
1
89
0
1
Order By: Relevance
“…New TKIs have been designed to overcome ABL1 gatekeeper mutations (mainly T315I) and at present are only preclinically validated inhibitors, such as Bafetinib, Rebastinib, Tozasertib, and Danusertib [ 248 ]. Other new molecules are already under clinical trials e.g., PF-114, HQP1351 (Olverembatinib), and K0706 (Vodobatinib), which function competitively as inhibitors of BCR-ABL1 TK at the ATP-binding site ( Table 2 ) [ 249 ]. These inhibitors have presented an increased potency against a wide range of BCR-ABL1 mutations [ 249 , 250 , 251 , 252 ] and may overcome some the limitations of approved TKIs.…”
Section: Therapeutic Approaches Against Resistancementioning
confidence: 99%
“…New TKIs have been designed to overcome ABL1 gatekeeper mutations (mainly T315I) and at present are only preclinically validated inhibitors, such as Bafetinib, Rebastinib, Tozasertib, and Danusertib [ 248 ]. Other new molecules are already under clinical trials e.g., PF-114, HQP1351 (Olverembatinib), and K0706 (Vodobatinib), which function competitively as inhibitors of BCR-ABL1 TK at the ATP-binding site ( Table 2 ) [ 249 ]. These inhibitors have presented an increased potency against a wide range of BCR-ABL1 mutations [ 249 , 250 , 251 , 252 ] and may overcome some the limitations of approved TKIs.…”
Section: Therapeutic Approaches Against Resistancementioning
confidence: 99%
“…Growth characteristics (Supplementary Figure S2) together with proliferation analyses (Figure 2, Table 2) demonstrate that all the resistant cells decreased their sensitivity to TKIs as compared to their sensitive counterparts. The observed cross-resistance (insensitivity of the cells to another TKI than that used for resistance acquisition) confirms that the resistance mechanisms developed under the selective pressure of one inhibitor often provide resistance to other TKIs as well 61 .…”
Section: Discussionmentioning
confidence: 65%
“…More importantly, 40%-60% of patients who attained deep and durable molecular responses successfully maintained remission after TKI discontinuation. 12 , 22 , 23 , 68 Numerous studies have identified correlations between TFR and the cellular immune system, including a higher number of NK cells and a lower Treg proportion, as previously mentioned, compared with patients who show disease relapse or transformation, suggesting that TFR is based on immune regulation and should be considered to identify promising immunotherapeutic targets, allowing more patients to achieve successful TKI cessation. 81 , 82 , 91 , 92 However, to further evaluate the impact of the immune system on TFR, additional immunological parameters must be studied, preferably quantified, to determine the optimal therapeutic endpoint for successful TFR.…”
Section: What Is a Better Methods Of Management?mentioning
confidence: 89%
“…The subsequent introduction of ponatinib, which is effective in patients with genetic abnormalities that make them resistant to TKIs, has further improved treatment outcomes, and the overall survival rate is up to 90%. 6−10 12 …”
Section: Introductionmentioning
confidence: 99%